Gender and Cultural Mediation in the Long Eighteenth Century Women across Borders - Bolufer, Mónica; Guinot-Ferri, Laura; Blutrach, Carolina (New Transculturalisms, 1400-1800, 2024)
This open access book explores the transnational and transoceanic dimensions of the debate on gender and women's cultural agency and mediation in the long eighteenth century. It aims to decenter perspectives on traditional Enlightenment geographies, by emphasizing cultural transfers between Southern Europe and the rest of Europe, as well as with the Americas; by focusing on a variety of cultural mediators-women authors, female (and male) translators, readers, travelers, and disseminators; and by examining diverse written and visual sources-from correspondence, travel narratives, and philosophical essays, to novels, opera, portraits. Mónica Bolufer is Professor of Modern History at the University of Valencia, Spain. She is the Principal Investigator of the ERC-funded research project CIRGEN: Circulating Gender in the Global Enlightenment: Ideas, Networks, Agencies. Laura Guinot-Ferri is Postdoctoral Researcher at the University of Valencia, Spain, and part of the CIRGEN team. Carolina Blutrach is Senior Postdoctoral Researcher at the University of Valencia, Spain, and part of the CIRGEN team.